Corporate innovation strategy and performance improvement an empirical analysis based on the digital ERA - Duan, Xinhua; Li, Sheng (Edelweiss Applied Science and Technology, 2025)
In the context of a rapidly changing global business environment, innovation has become a crucial driver of sustainable growth and competitive advantage for enterprises. With the widespread application of digital technology, understanding how companies can enhance their performance through innovation strategies has become an important area of research. The study reveals that (1) innovation strategy has a significant positive impact on firm performance, and that increased R&D investment and the promotion of management innovation contribute to improved profitability; (2) digital technology plays a positive moderating role between innovation strategy and firm performance, with firms experiencing higher returns on innovation investments after adopting digital tools; and (3) the industrial environment and firm size have heterogeneous effects on the effectiveness of innovation strategies, with larger firms more likely to benefit from such strategies compared to small and medium-sized enterprises.